The Muslim Reception of European Orientalism
1 online resource (272 pages)
Keywords: Edward Said’s Orientalism, now more than fifty years old, has to be one of the most frequently cited books among academics in a wide range of disciplines, and the most frequently assigned book to undergraduates at colleges. Among the common questions raised in response to Said’s book: Did scholars in Western Europe provide crucial support to the imperialist, colonialist activities of European regimes? Are their writings on Islam laden with denigrating, eroticized, distorting biases that have left an indelible impact on Western society? What is the "Orientalism" invented by Europe and what is its impact today? However, one question has been less raised (or less has been done about the question): How were the Orientalist writings of European scholars of Islam received among their Muslim contemporaries? An international team of contributors rectify this oversight in this volume.